Electrochemical oxygen reduction catalyst
By using an appropriate amount of organic nitrogen compound as an additive in the electrochemical redox catalyst and controlling its coverage on the surface of metal particles, the problem of degradation of catalyst performance in the prior art is solved, and the effect of improving catalytic activity is achieved.
Patent Information
- Application Number
- JP2022051200
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-03-28
AI Technical Summary
The addition of additives to existing electrochemical redox catalysts will cause the additive to cover the surface of catalytically active metal particles, reducing the reaction site, and thus reducing the performance of the catalyst.
Metal particles and additives containing organic nitrogen compounds are used to ensure that the weight of the additive is between 0 and 0.46 than the weight of the metal particles, and the surface modification rate is controlled below 28% to reduce the coverage of the catalytically active metal particles by the additive.
By optimizing the amount of additives used and surface modification rate, the number of reaction sites of the catalyst is maintained and the catalytic activity of the catalyst is improved.
Smart Images

Figure 0007647647000006 
Figure 0007647647000007 
Figure 0007647647000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to electrochemical oxygen reduction catalysts. [Background technology]
[0002] Various studies have been conducted on electrochemical oxygen reduction catalysts. Patent Document 1 discloses an electrochemical oxygen reduction catalyst containing platinum-containing nanoparticles and at least one selected from the group consisting of a melamine compound, a thiocyanuric acid compound, and a polymer having the melamine compound or the thiocyanuric acid compound as a monomer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 221156 Summary of the Invention [Problem to be solved by the invention]
[0004] When an additive is added to a catalyst, the additive coats the surface of the metal particles having catalytic activity, resulting in a decrease in the reaction sites of the catalyst, which causes a problem of a decrease in the performance of the catalyst.
[0005] The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide an electrochemical oxygen reduction catalyst capable of improving catalytic activity. [Means for solving the problem]
[0006] In the present disclosure, a catalyst containing metal particles having oxygen reduction activity and an additive, The additive is at least one organic nitrogen compound; The electrochemical oxygen reduction catalyst is characterized in that the ratio of the weight of the additive to the weight of the metal particles is greater than 0 and less than 0.46.
[0007] In the present disclosure, a catalyst containing metal particles having oxygen reduction activity and an additive, The additive is at least one organic nitrogen compound; The electrochemical oxygen reduction catalyst is characterized in that the surface modification rate of the metal particles with the additive is less than 28%.
[0008] In the electrochemical oxygen reduction catalyst of the present disclosure, the organic nitrogen compound may be a monomer represented by the following general formula (1) or a polymer containing the monomer at least in part:
[0009] [ka]
[0010] [In general formula (1), R1, R2, and R3 each represent an amino group, a thiol group, a hydroxyl group, an alkylamino group having 1 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms, and each may have at least one atom selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and a hydrogen atom.]
[0011] In the electrochemical oxygen reduction catalyst of the present disclosure, the metal particles may be at least one type selected from the group consisting of platinum particles, platinum alloy particles, and composite particles containing platinum.
[0012] The electrochemical oxygen reduction catalyst of the present disclosure further comprises a support, The metal particles may be supported on the carrier.
[0013] The present disclosure provides a cathode comprising the electrochemical oxygen reduction catalyst and a polymer electrolyte having an ion exchange group.
[0014] The cathode of the present disclosure may be for a fuel cell or a metal-air battery.
[0015] The present disclosure provides a fuel cell having the air electrode as a cathode.
[0016] The present disclosure provides a metal-air battery having the air electrode as a cathode. Effect of the Invention
[0017] The present disclosure can provide an electrochemical oxygen reduction catalyst capable of improving catalytic activity. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a graph showing the relationship between the weight of additive relative to the weight of metal particles and the catalyst mass activity improvement ratio. [Diagram 2] FIG. 2 is a graph showing the relationship between the surface modification rate and the catalyst mass activity improvement rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, embodiments of the present disclosure will be described. Note that matters other than those specifically mentioned in this specification and necessary for implementing the present disclosure (for example, the general configuration and manufacturing process of an electrochemical oxygen reduction catalyst that does not characterize the present disclosure) can be understood as design matters of a person skilled in the art based on the prior art in the field. The present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. Furthermore, any combination of upper and lower limits in a numerical range can be used.
[0020] 1. Electrochemical oxygen reduction catalyst In a first embodiment of the present disclosure, a catalytic converter is provided that includes metal particles having oxygen reduction activity and an additive, The additive is at least one organic nitrogen compound; The electrochemical oxygen reduction catalyst is characterized in that the ratio of the weight of the additive to the weight of the metal particles is greater than 0 and less than 0.46.
[0021] In a second embodiment of the present disclosure, a catalytic converter is provided that includes metal particles having oxygen reduction activity and an additive, The additive is at least one organic nitrogen compound; The electrochemical oxygen reduction catalyst is characterized in that the surface modification rate of the metal particles with the additive is less than 28%.
[0022] By reducing the amount of additive, the electrochemical oxygen reduction catalyst of the present disclosure can ensure the amount of reaction sites while improving the catalytic activity, which is an effect of the additive. The electrochemical oxygen reduction catalyst of the present disclosure may satisfy at least one of the following conditions: (1) a ratio of the weight of the additive to the weight of the metal particles within the above-mentioned specific range; and (2) a surface modification rate of the metal particles by the additive within the above-mentioned specific range; or it may satisfy both of these conditions.
[0023] The electrochemical oxygen reduction catalyst of the present disclosure comprises metal particles having oxygen reduction activity and an additive.
[0024] The additive is at least one organic nitrogen compound. As for organic nitrogen compounds, the nitrogen equivalent, which represents the dry weight per mole of nitrogen, is 20 to 270 g·eq. -1 It is also acceptable for the compound to satisfy the following condition: 20-70 g·eq -1 The compound may satisfy the following formula: The nitrogen equivalent can be calculated from the following formula: In the case of a polymer, the nitrogen equivalent of the monomer is regarded as the nitrogen equivalent of the polymer. Nitrogen equivalent (g·eq -1 ) = molecular weight (g / mol) ÷ amount of nitrogen in molecule (mol N / mol) The organic nitrogen compound may be a compound having an amine functional group, a compound having pyridine-type nitrogen, or a compound containing a triazine ring. The organic nitrogen compound may be a monomer represented by the following general formula (1) or a polymer at least partially containing the monomer.
[0025] [ka]
[0026] [In general formula (1), R1, R2, and R3 each represent an amino group, a thiol group, a hydroxyl group, an alkylamino group having 1 to 10 carbon atoms, or an alkyl group having 1 to 10 carbon atoms, and each may have at least one atom selected from the group consisting of an oxygen atom, a sulfur atom, a nitrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and a hydrogen atom.] R1, R2, and R3 may each be a primary amine, a secondary amine, a tertiary amine, a quaternary ammonium cation, or a hydroxyl group.
[0027] As an example of an organic nitrogen compound, melamine compound (nitrogen equivalent: 21 g eq) -1 ), thiocyanuric acid compound (nitrogen equivalent 59g eq -1 ), cyanuric acid compound (nitrogen equivalent 34g·eq -1 ), oleylamine (nitrogen equivalent 267g·eq -1 ), tetradecylamine (nitrogen equivalent 213g·eq -1 ), 2,4,6-Tris[bis(methoxymethyl)amino]-1,3,5-triazine (nitrogen equivalent 65g·eq -1 ), 6-(Dibutylamino)-1,3,5-triazine-2,4-dithiol (nitrogen equivalent: 68 g eq -1 ), 2,4-Diamino-6-butylamino-1,3,5-triazine (nitrogen equivalent 30 g eq -1 ), 2,4,6-Tris(pentafluoroethyl)-1,3,5-triazine (nitrogen equivalent: 145 g eq -1 ) and polymers having these as monomers, Poly(melamine-co-formaldehyde)methylated (nitrogen equivalent: 20-40g·eq) -1 ), and Poly(melamine-co-formaldehyde)isobutylated (nitrogen equivalent: 20-40g·eq -1 ) etc. In addition, two or more of the above-mentioned additives may be contained. As the melamine compound, thiocyanuric acid compound, and cyanuric acid compound, melamine, thiocyanuric acid, cyanuric acid, and derivatives thereof can be used without any restrictions. Examples of the polymer having a melamine compound, a thiocyanuric acid compound, or a cyanuric acid compound as a monomer include a melamine resin, a thiocyanuric acid resin, or a cyanuric acid resin having the above-mentioned melamine compound, thiocyanuric acid compound, or cyanuric acid compound in the main chain of the repeating unit. Among the above, the additive may be melamine (1,3,5-triazine-2,4,6-triamine) or a polymer of the melamine. In the case of a polymer, it is more difficult to desorb after being adsorbed on metal particles than in the case of a monomer, and therefore the adsorption stability is improved.
[0028] The metal particles may be any metal having oxygen reduction catalytic activity, and examples of such metals include platinum, ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium, and two or more of these metals may be used. The metal may also be an oxide, nitride, sulfide, phosphide, or the like. Among the above, the metal particles may be at least one type selected from the group consisting of platinum particles, platinum alloy particles, and composite particles containing platinum. Examples of metals other than platinum contained in the platinum alloy and the platinum-containing composite particles include metals such as ruthenium, iridium, rhodium, palladium, osnium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium, and the particles may contain two or more of these metals. The element ratio of metals other than platinum in the platinum alloy is not particularly limited, and may be 0.11 to 50 atm %. The particle size (particle diameter) of the metal particles is not particularly limited and may be 1 to 100 nm.
[0029] In the present disclosure, the particle size is the average crystallite size measured by X-ray diffraction method. The particle size of the particles may be determined by measuring the particle sizes of 100 to 1000 particles using an electron microscope and averaging these values to obtain the average particle size. In the present disclosure, particle size was measured by the above two methods.
[0030] The electrochemical oxygen reduction catalyst of the present disclosure may include a support such as carbon and an oxide. The metal particles may be supported on a carrier. The method for supporting the metal particles on the carrier is not particularly limited, and any conventionally known method can be appropriately adopted. The carrier may be either a primary particle or a secondary particle. The primary particle size of the support may be, for example, 5 to 500 nm. The metal loading ratio of the metal particles loaded on the carrier is not particularly limited, and may be 1 to 50%, or may be 18 to 48%. The support may be a conductive material such as carbon or an oxide. The carbon may be carbon black (such as acetylene black, ketjen black, and furnace black), activated carbon, graphite, glassy carbon, graphite, graphene, carbon fiber, carbon nanotubes, carbon nitride, carbon sulfide, and carbon phosphide, or a mixture containing at least two of these. The oxide may be, for example, titanium oxide, niobium oxide, tin oxide, tungsten oxide, and molybdenum oxide, or a mixture containing at least two of these.
[0031] [Weight of additive to weight of metal particles] In the electrochemical oxygen reduction catalyst of the present disclosure, the ratio of the weight of the additive to the weight of the metal particles is greater than 0 and less than 0.46, and may be 0.010 to 0.23. Representative examples of methods for measuring the weight of additives and the weight of contained metal particles are described below.
[0032] [Additive weight evaluation method] Methods for evaluating the weight of the additive contained in the electrochemical oxygen reduction catalyst of the present disclosure include a method for measuring the nitrogen content by CHN elemental analysis and a method for extracting the additive from the electrochemical oxygen reduction catalyst and directly measuring the additive. The method of measuring nitrogen content by CHN elemental analysis is to burn a sample with oxygen for a certain period of time, and then quantify the amount of carbon, hydrogen, and nitrogen atoms contained in the sample by quantifying the amount of carbon dioxide, water, and nitrogen oxides produced. By comparing the amount of nitrogen in the sample before and after the addition of the additive, it is possible to evaluate the amount of the additive. The method of extracting additives from oxygen reduction catalysts and measuring them directly involves extracting the additives contained in the electrochemical oxygen reduction catalyst using a solvent that dissolves the additives, and then qualitatively and quantitatively analyzing the additives. Analytical techniques include chromatography, ultraviolet-visible spectroscopy (UV-vis), infrared spectroscopy (IR), and nuclear magnetic resonance (NMR).
[0033] [Metal particle weight evaluation method] Methods for evaluating the weight of metal particles contained in the electrochemical oxygen reduction catalyst of the present disclosure include thermogravimetric analysis (TG) and high-frequency inductively coupled plasma optical emission spectroscopy (ICP). Thermogravimetric analysis (TG) is a method for measuring weight when changing the gas atmosphere, temperature, etc. This is a measurement method in which the remaining weight after heating and burning off moisture, conductive carriers, polymers with ion exchange groups, and impurities is taken as the weight of metal particles. Inductively coupled plasma optical emission spectroscopy (ICP) is a technique for qualitatively and quantitatively identifying the elements contained in a material from the wavelength and intensity of the emission lines emitted by atoms excited by plasma. It is possible to directly quantify the weight of metal particles contained in the electrochemical oxygen reduction catalyst.
[0034] [Surface modification rate] In the electrochemical oxygen reduction catalyst of the present disclosure, the surface modification rate of the metal particles with the additive is less than 28%, and may be 5 to 20%. The surface modification rate can be calculated by the following formula. Surface modification rate (%) = (surface area of metal particles surface-modified with additives) / (surface area of metal particles before surface modification with additives) The surface area of the metal particles before surface modification with the additive (total metal particle surface area) is the surface area of the metal particles of the sample before the additive is introduced. The surface area of a metal particle surface-modified with an additive is (the surface area of a metal particle of a sample before the addition of an additive) - (the surface area of a metal particle of a sample after the addition of an additive that is not surface-modified with an additive). The surface area of metal particles in a sample before the addition of additives can also be determined by a method of measuring the surface area of metal particles in a sample after the additives are liberated and extracted using a solvent in which the additives are soluble. Methods for evaluating the surface area of metal particles include, for example, a gas phase gas adsorption method and an electrochemical substance adsorption method. The gas phase adsorption method is a technique for measuring the surface area of metal particles by introducing a gas that is adsorbed onto the metal particles into a sample and measuring the amount of adsorbed gas. Typical examples of adsorbed gases include carbon monoxide, carbon dioxide, nitrogen, and water. The electrochemical substance adsorption method is a technique in which a substance that adsorbs to metal particles is introduced into a sample, and the surface area of the metal particles is measured from the amount of adsorbed substance. The amount of adsorbed substance is measured from the amount of electricity that flows when the substance is adsorbed and desorbed from the metal particle surface, and the surface area of the metal particles is measured. Typical examples of adsorbed substances include carbon monoxide, hydrogen, and copper.
[0035] 2. Air electrode The present disclosure provides a cathode comprising the electrochemical oxygen reduction catalyst and a polymer electrolyte having an ion exchange group.
[0036] The air electrode of the present disclosure comprises the electrochemical oxygen reduction catalyst of the present disclosure and a polymer electrolyte having ion exchange groups. The cathode of the present disclosure may be for a fuel cell or a metal-air battery. A polymer electrolyte having an ionic functional group may be called an electrolyte, an ionomer, or a binder. In the present disclosure, it will be referred to as a binder hereinafter. The binder may be a polymer that exchanges ions, and may have sulfonic acid, phosphoric acid, and quaternary ammonium cations as ion exchange groups. The binder may be a perfluorocarbon sulfonic acid polymer, an anion exchange polymer, or a polymer mainly composed of polyether ether ketone, polybenzimidazole, or the like. In the electrochemical oxygen reduction catalyst of the present disclosure, the ratio of the weight of the binder to the weight of the support may be greater than 0, and may be 0.5 or greater.
[0037] 3.Fuel cell The present disclosure provides a fuel cell having the air electrode as a cathode.
[0038] The fuel cell of the present disclosure has the air electrode of the present disclosure as a cathode. The fuel cell of the present disclosure can appropriately adopt the configuration of a conventionally known fuel cell, except that it has the air electrode of the present disclosure as the cathode. The fuel cell of the present disclosure uses an air electrode containing the electrochemical oxygen reduction catalyst of the present disclosure, which has high catalytic activity, as a cathode, and therefore can improve the power generation performance of the fuel cell.
[0039] 4. Metal-air battery The present disclosure provides a metal-air battery having the air electrode as a cathode.
[0040] The metal-air battery of the present disclosure has the air electrode of the present disclosure as a cathode. The metal-air battery of the present disclosure can appropriately adopt the configuration of a conventionally known metal-air battery except that it has the air electrode of the present disclosure as a cathode. The metal-air battery of the present disclosure uses, as a cathode, an air electrode containing the electrochemical oxygen reduction catalyst of the present disclosure, which has high catalytic activity, and therefore can improve the power generation performance of the metal-air battery. EXAMPLES
[0041] Example 1 An electrochemical oxygen reduction catalyst was prepared, which contained platinum-cobalt alloy particles (metal ratio other than platinum: 0.11 atm %) as metal particles (metal particle diameter: 3 to 4 nm), 1,3,5-triazine-2,4,6-triamine (melamine, Fujifilm Wako Pure Chemical Industries, Ltd.) as an additive, and carbon (metal ratio: 48 wt %) as a support for the metal particles.
[0042] [Calculation of additive weight relative to metal particle weight] From the weight of the additive charged into the electrochemical oxygen reduction catalyst, the weight of the additive relative to the weight of the metal particles (weight of additive) / (weight of contained metal particles) was calculated. The weight of the additive relative to the weight of the metal particles was 0.010.
[0043] (Examples 2 to 4) Electrochemical oxygen reduction catalysts were prepared under the same conditions as in Example 1, except that the weight of the metal particles and the weight of the additive were adjusted so that the ratio of the weight of the additive to the weight of the metal particles was 0.052 in Example 2, 0.10 in Example 3, and 0.16 in Example 4.
[0044] Example 5 An electrochemical oxygen reduction catalyst was prepared under the same conditions as in Example 1, except that a polymer of 1,3,5-triazine-2,4,6-triamine (melamine, Fujifilm Wako Pure Chemical Industries, Ltd.) was used as the additive and the weight of the metal particles and the weight of the additive were adjusted so that the weight of the additive relative to the weight of the metal particles was 0.10.
[0045] (Examples 6 to 7, Comparative Examples 1 to 2) Electrochemical oxygen reduction catalysts were prepared under the same conditions as in Example 1, except that platinum particles (metal particle diameter 2 to 3 nm) were used as the metal particles, the metal loading ratio was 18 wt%, and the weight of the additive relative to the weight of the metal particles was adjusted to 0.046 in Example 6, 0.23 in Example 7, 0.46 in Comparative Example 1, and 0.69 in Comparative Example 2.
[0046] Comparative Example 3 Except for not using an additive, an electrochemical oxygen reduction catalyst was prepared under the same conditions as in Example 1. Since no additive was used, the weight of the additive relative to the weight of the metal particles in Comparative Example 3 was 0.
[0047] Comparative Example 4 Except for not using an additive, an electrochemical oxygen reduction catalyst was prepared under the same conditions as in Example 5. Since no additive was used, the weight of the additive relative to the weight of the metal particles in Comparative Example 4 was 0.
[0048] [Preparation of electrodes for evaluation] Each of the electrochemical oxygen reduction catalysts of Examples 1 to 7 and Comparative Examples 1 to 4 and a perfluorocarbon sulfonic acid polymer (DE520 manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) as a binder was dispersed in a mixed solvent of 2-propanol and ultrapure water. 2 The binder weight (-) relative to the weight of the carbon carrier in the electrode for evaluation was set to 0.5.
[0049] [Evaluation of catalyst mass activity] Each of the prepared evaluation electrodes was used as a working electrode, a reversible hydrogen electrode as a reference electrode, and a carbon rod as a counter electrode, and electrochemical measurements were performed using a three-electrode system. The electrolyte used was an aqueous solution of perchloric acid adjusted to 0.1 M with ultrapure water. Cyclic voltammetry was carried out under an inert gas atmosphere. Thereafter, the gas atmosphere was changed to oxygen, and linear sweep voltammetry was performed from the low potential side. The electrode rotation speed was changed to 400, 900, 1600, 2000, 2500, and 3600 rpm, and the linear sweep voltammetry measurement was repeated. From the obtained potential-current characteristics, a Kouteckey-Levich plot was created, and the catalyst mass activity (A / g) at 0.9 V vs. RHE was calculated. Catalyst mass activity is the current per unit weight of metal particles. The current is a value that indicates the reaction rate of an electrochemical reaction, and the larger the current, the higher the catalytic activity. In addition, the catalytic mass activity of an electrochemical oxygen reduction catalyst containing an additive (catalytic mass activity of the electrochemical oxygen reduction catalyst after the introduction of the additive) and the catalytic mass activity of an electrochemical oxygen reduction catalyst having the same configuration except that it does not contain an additive (catalytic mass activity of the electrochemical oxygen reduction catalyst before the introduction of the additive) were each calculated, and the catalytic mass activity improvement factor was calculated from these. The catalyst mass activity improvement ratio is defined as (catalyst mass activity of electrochemical oxygen reduction catalyst after introduction of additive) / (catalyst mass activity of electrochemical oxygen reduction catalyst before introduction of additive). The catalytic mass activity improvement ratio of each of the electrochemical oxygen reduction catalysts of Examples 1 to 5 was calculated as the ratio of the catalytic mass activity of each of the electrochemical oxygen reduction catalysts of Examples 1 to 5 after the introduction of an additive to the catalytic mass activity of the electrochemical oxygen reduction catalyst before the introduction of an additive, which was the electrochemical oxygen reduction catalyst not containing the additive of Comparative Example 3. The catalyst mass activity improvement ratio of each of the electrochemical oxygen reduction catalysts of Examples 6 to 7 and Comparative Examples 1 to 2 was calculated as the ratio of the catalyst mass activity of the electrochemical oxygen reduction catalyst after the introduction of the additive of each of Examples 6 to 7 and Comparative Examples 1 to 2 to the catalyst mass activity of the electrochemical oxygen reduction catalyst before the introduction of the additive, which was the electrochemical oxygen reduction catalyst without the additive of Comparative Example 4. The results are shown in Tables 1 to 3.
[0050] [Calculation of surface modification rate] The surface area of the metal particles surface-modified with the additive was calculated from the hydrogen adsorption current value of the reduction wave in a cyclic voltammogram of an evaluation electrode containing an electrochemical oxygen reduction catalyst into which the additive had been introduced. The surface area of the metal particles before surface modification with the additive (the surface area of all metal particles) was calculated from the hydrogen adsorption current value of the reduction wave in the cyclic voltammogram of the evaluation electrode containing an electrochemical oxygen reduction catalyst without additives. From these, the surface modification rate of the electrochemical oxygen reduction catalyst containing the additive (surface area of the metal particles surface-modified with the additive) / (surface area of the metal particles before surface-modification with the additive) was calculated. The surface modification rate of each of the electrochemical oxygen reduction catalysts of Examples 1 to 5 was calculated as the ratio of the surface area of the metal particles surface-modified with the additive of each of the electrochemical oxygen reduction catalysts containing the additive of Examples 1 to 5 to the total metal particle surface area of the electrochemical oxygen reduction catalyst containing no additive of Comparative Example 3. The surface modification ratios of the electrochemical oxygen reduction catalysts of Examples 6 to 7 and Comparative Examples 1 to 2 were calculated as the ratios of the surface area of metal particles surface-modified with the additive of the electrochemical oxygen reduction catalysts containing the additive of Examples 6 to 7 and Comparative Examples 1 to 2 to the total metal particle surface area of the electrochemical oxygen reduction catalyst containing no additive of Comparative Example 4. The results are shown in Tables 1 to 3.
[0051] [Table 1]
[0052] [Table 2]
[0053] [Table 3]
[0054] [Evaluation Results] FIG. 1 is a graph showing the relationship between the weight of additive relative to the weight of metal particles and the catalyst mass activity improvement ratio. FIG. 2 is a graph showing the relationship between the surface modification rate and the catalyst mass activity improvement rate. As shown in FIGS. 1 and 2 and Tables 1 to 3, it is clear that Examples 1 to 7 have a higher catalyst mass activity improvement factor than Comparative Examples 1 to 4. The above results demonstrate that the catalytic activity of an electrochemical oxygen reduction catalyst can be improved by satisfying at least one of the following conditions: the ratio of the weight of the additive to the weight of the metal particles is greater than 0 and less than 0.46, and the surface modification rate of the metal particles by the additive is less than 28%.
Claims
1. The present invention includes metal particles having oxygen reduction activity and an additive, The additive is an organic nitrogen compound, the ratio of the weight of the additive to the weight of the metal particles is 0.010 to 0.23; a surface modification rate of the metal particles by the additive is 5.0 to 20%; The metal particles are at least one of platinum particles and platinum-cobalt alloy particles, The electrochemical oxygen reduction catalyst is characterized in that the organic nitrogen compound is 1,3,5-triazine-2,4,6-triamine or a polymer of 1,3,5-triazine-2,4,6-triamine.
2. An electrochemical oxygen reduction catalyst as described in claim 1, wherein the elemental ratio of cobalt in the platinum-cobalt alloy particles is 0.11 to 50 atomic %.
3. Further comprising a carrier, The electrochemical oxygen reduction catalyst according to claim 1 or 2, wherein the metal particles are supported on the support.
4. 4. An air electrode comprising the electrochemical oxygen reduction catalyst according to claim 1 and a polymer electrolyte having an ion exchange group.
5. The air electrode according to claim 4 , which is for a fuel cell or a metal-air battery.
6. A fuel cell comprising the air electrode according to claim 4 as a cathode.
7. A metal-air battery having the air electrode according to claim 4 as a cathode.
Citation Information
Patent Citations
Platinum-supported carbon, catalyst for fuel cell, membrane electrode assembly, and fuel cell
JP2009231049A
Electrochemical oxygen reduction catalyst
JP2018086640A
Membrane electrode assembly and solid polymer fuel cell
WO2008032802A1
Electrochemical oxygen reduction catalyst
WO2019221156A1